O Kraksnoludkach i o sierotce Marysi - Konopnicka, Maria, 1842-1910.; Szancer, Jan Marcin, 1902-1973. (Poznan : GMP, 1994)
A fairy tale about elves and an orphaned girl, Marysi. For ages 7-10.
Keywords: Fairy tales -- Poland